PEMBELAJARAN MULTIMEDIA - Lestari, Ambar Sri (Institut Agama Islam Negeri Kendari, 2013)
Multimedia is a combination of text, graphics, animation,sound and video. The combination of multiple mediapreviously done manually, such as slide projector and tape.Today's media mix has been emphasized as a driver ofoverall computer control combined media. Thus the meaningof a multimedia, commonly known today is a combination ofvarious graphics, text, voice, video and animation. Thebusiness case is an entity that is jointly display information,messaging and content.Key Words: Multimedia, Learning.